Muslim American politics and the future of US democracy - Curtis, Edward E. (NYU Press, 2019)
The political assimilation of Muslim Americans -- The Nation of Islam and the cold war liberal consensus -- Malcolm X and the Islamic politics of global Black liberation -- The transnational ethics of four Muslim American women in Jordan -- Blood sacrifice and the myth of the fallen Muslim soldier in U.S. presidential elections after 9/11.